Efficacy of rodenticide baits with decreased concentrations of brodifacoum: Validation of the impact of the new EU anticoagulant regulation - Fraňková, M; Stejskal, Václav; Aulický, Radek (Scientific reports, 2019)
Anticoagulants are the most frequently used rodenticides at the global scale. Because of their persistency, bioaccumulation and potential for secondary intoxication, they have faced increasing legislative regulations. Recently, the European Union Regulation (EU) 2016/1179 resulted in the production and application of rodenticides with nearly half dose (<30 ppm) of anticoagulants. However, published data on the biological efficacy of rodenticides with decreased doses are scarce in the EU. Therefore, this work compared the efficacy of the original high-dose (50 ppm) and new low-dose (25 ppm) brodifacoum-based baits in the offspring of wild-caught house mice (Mus musculus L.). In the no-choice laboratory feeding tests, 100% animals died in all treated groups and 0% died in the control groups. The achieved time to death did not differ between the original and low-dose baits across both types of feeding trials/regimes. The low-dose baits (25 ppm) were consequently tested under field conditions in two populations showing 95.7% and 99.8% efficacy. The obtained results highlighted the good efficacy of the new baits based on low-dose brodifacoum in non-resistant mouse populations. However, further validation is required regarding the remaining anticoagulant compounds and resistant rodent populations.
Keywords: antikoagulancia; Animals; 4-hydroxykumariny; Female; Mortality; ženské pohlaví; Legislation, Drug; Animal Feed; Anticoagulants; Mice; Evropská unie; zákonodárství lékové; mortalita; myši; Drug Dosage Calculations; Male; European Union; krmivo pro zvířata; Rodenticides; 4-Hydroxycoumarins; zvířata; mužské pohlaví; rodenticidy; výpočet dávky léku